The Relevance of Azeez Sanni and Segun Awosiyan Newspaper Cartooning in Nigeria - Adeyemi, Adedola Olayinka; Afolabi, Benjamin Eni-Itan F.; Sobowale, Tolulope Oladimeji; Adeloye, Adebayo Abiodun; Odewole, Peter Oluwagbenga (NIU Journal of Social Sciences, 2024)
This paper articulates the relevance of newspaper cartooning in Nigeria through which, the forms, styles and character composition of selected cartoonists works were looked into. The study examined the works of Azeez Sanni and Segun Awosiyan who over the years have contributed their quota immensely in Nigeria newspaper cartooning. However, despite their impact in the study area, they are not known in scholarly works. Hence this study which purposively selected five works each from the two cartoonists with a view to looking at their cartoons impact on Nigeria socio-cultural and political issues, without jettisoning Government reaction on the embedded information’s carried in their cartoons. In achieving this, descriptive, formal and expressive content was adopted to appraise the purposively selected cartoons of the artists. Keywords: Pre-Colonia, Political, Cartoon, Newspaper and Socio-Cultural